Correction to: PAKs supplement improves immune status and body composition but not muscle strength in resistance trained individuals - Frederico Gerlinger-Romero; Fabio S. Lira; Fernando A. Marques; Paulo C. Muzy; Rodolfo A. N. Peres; Érico C. Caperuto (Taylor & Francis Group, 2018)
The original article [1] contains an error whereby the author, Frederico G Romero's name is displayed incorrectly; the correct spelling is instead displayed in this Correction article.